Acute toxicity test combination of binahong leaves extract (Anredera cordifolia) and catfish oil (Pangasius micronema Blkr.) in mice - Rahma Shabrina Auliya; Meitasari Annisa Diyan; Sasongko Heru (BIO Web of Conferences)
Binahong (Anredera cordifolia) and catfish (Pangasius micronema Blkr.) plants have been proven to have pharmacological effects through various studies. However, there has been no research on the toxicity level of the combination of two ingredients. The purpose of this study was to determine the acute toxicity after administration of the combination of natural extracts, the LD50, and the toxicity category of the compound. The parameters observed were symptoms of toxicity, changes in body weight, and changes in organ weight of mice for 14 days of observation. The combination of binahong extract with catfish oil was given orally in graded doses, namely group I (250 mg/kg catfish oil and 100 mg/kg binahong), group II (500 mg/kg catfish oil and 200 mg/kg binahong), and group III (1000 mg/kg catfish oil and 400 mg/kg binahong). The data obtained were then subjected to an ANOVA test to determine differences between the test groups. The results showed that the symptoms of toxicity that appeared, body weight testing, and organs of the liver, heart, and kidneys of mice obtained a significance value of p>0.05 so there is no significant difference between the weight of mice’s hearts. The LD50 value in this study is a pseudo-LD50 because there is no death in all test animals. This shows that the combination of binahong extract and catfish oil is categorized as practically non-toxic with LD50 > 5000 mg/kg.